The Influence of Social Media on University Students' Choice 0f Presidential Candidates in 2024 - Laurencia Primawati Degodona; Rajagukguk, Jonson; Sarumaha, Zeni Oktavianis (Tunas Geografi, 2025)
Social media has become a primary tool in influencing voter decisions, especially among young generations, in the 2024 Election. With a creative and interactive approach, platforms such as TikTok dominate in delivering political messages to university students, who are part of the millennial and Gen Z generations. This research employs a quantitative descriptive method using questionnaires on 120 students from HKBP Nommensen University to measure the influence of social media on the decision to vote for presidential and vice-presidential candidates. The hypothesis test results indicate a significant influence of social media on students' voting decisions. 70.9% of respondents consider social media as the main factor influencing their choice, with TikTok being the most influential platform (74.2%). Additionally, entertaining and creative political slogans such as "Ok Gas 02 Tabrak-Tabrak Masuk" influenced 57.5% of respondents. These findings support the hypothesis that social media significantly affects voting decisions. The significance value in the ANOVA test is 0.001 (< 0.05), indicating that the regression model is significant. Therefore, the alternative hypothesis (Hₐ) is accepted, meaning there is an essential influence between the use of social media and voting decisions, with a contribution of 78.1%. This reinforces the importance of political communication strategies based on social media with engaging and informative content. Indonesia's 2024 election demonstrates how social media, especially TikTok, shapes young voters' preferences by transcending regional boundaries and creating new spaces for political engagement.